Gas turbine control : Modifications for: availability and limitation of spinning reserve and limitation of non-desired unloading - Agüero, Jorge Luis (2005)
This paper presents several modifications developed in a gas turbine control system. One of the modifications made in turbine control limits speed deviations to the governor. Consequently, this modification limits turbine power delivered -positive and negative- for Primary Control of Frequency purposes. In addition, this modification avoids that large, sudden power unloading takes place when the grid frequency recovers from a big dip, while original operational control modes are active. Together with complementary modifications made in the power plant centralized control, other turbine control modifications allow operators to adjust set points of grid frequency, dispatched power and required spinning reserve (positive and negative) which are established by the Dispatch Center of Argentinean electrical grid. Another modifications made in the power plant centralized control allows keeping the spinning reserve margins always available in spite of variations of maximum turbine power with weather conditions. These modifications were developed in a 120 MW gas turbine, which is part of a combined cycle in Tucumán, Argentina. Finally, several tests carried out on the turbine are presented together with operational records that were taken during system frequency disturbances. The tests and operational records show the behavior of the turbine power with and without the modifications made to its control system.